MENJAGA KEPERCAYAAN LEMBAGA PENDIDIKAN ISLAM MELALUI INTEGRITAS DAN AKUNTABILITAS PERSPEKTIF HADIS - Khairunnisa, Luthfi; F Ramdan, Dadan (Prodi Pendidikan Agama Islam, 2026)
Abstract Public trust is the main social capital for the sustainability and success of Islamic educational institutions amid social dynamics and increasingly complex governance demands. A common problem is the weakening of public trust due to low integrity and accountability in the management of educational institutions. This study aims to analyze efforts to maintain public trust in Islamic educational institutions through strengthening integrity values and implementing accountability based on the perspective of hadith. The research method used is a literature study with a qualitative-descriptive approach, through an examination of primary sources in the form of hadith, as well as supporting literature relevant to Islamic education management and ethics. The results of the study show that integrity, which is reflected in the values of trustworthiness, honesty, consistency, and exemplary behavior, as well as accountability, which is manifested through transparency, responsibility, and continuous evaluation, are fundamental principles in Islamic teachings. The synergistic integration of these two values has been proven to play a significant role in building and maintaining public trust in Islamic educational institutions.